Whole-abdominal IMRT for advanced ovarian carcinoma: Planning issues and feasibility - Jensen, Alexandra; Nill, Simeon; Rochet, Nathalie; Bendl, Rolf; Harms, Wolfgang; Huber, Peter E.; Debus, Jürgen; Münter, Marc (Physica medica, 2011)
Introduction - Despite enormous efforts to improve therapeutic strategies for patients with advanced ovarian carcinoma, outcome remains poor even with the advent cisplatinum-based chemotherapy regimen or taxanes with over 70% of patients developing local failure. Several trials were able to establish the potential benefit of adjuvant whole abdominal RT (WAI) though at the cost of sometimes marked side-effects. New technologies like IMRT have the potential of sparing normal tissues thus also potentially limiting treatment-related toxicity, hence a phase I trial was initiated to evaluate potential clinical benefit of WAI with IMRT. We intended to demonstrate that whole-abdominal IMRT is feasible and can be used in a routine clinical setting. - Methods - A water-equivalent phantom containing OARs was created simulating organ shape of the upper abdomen to investigate the necessary number of beams for the upper abdominal target irrespective of the number of segments and hence treatment times. We prescribed a total dose of 30 Gy in 1.5 Gy fractions to the median of the target. IMRT treatment plans for three patients with advanced ovarian cancer were created using 2 isocentres and between 12 and 14 beams while restricting the number of segments so as to restrict treatment times to less than 45 min. Dose to OARs such as kidneys and liver was strictly limited even below established maxima. - Results - In the phantom plans, no clear indication as to the optimum number of beams could be shown though there seems to be a slight trend toward a higher number of beams yielding better results. Examples demonstrating clinically inacceptable dose distributions for plans using only 9 beams. Acceptable treatment plans for real patients could be achieved using 12-14 beams and 2 isocentres. Treatment plans consisted of 264-286 segments resulting in an overall treatment time of approximately 37-45 min. Mean doses to the kidneys could be limited to 29.3% [23.1-33.2%] (right), and 26.8% [21-30.4%] (left). 50% of the liver received less than 72.4% [61-83%]. - Conclusion - IMRT for whole abdominal irradiation in patients with advanced ovarian carcinoma is applicable and feasible though treatment planning is complex and time-consuming. There is a significant reduction of dose to critical organs by using IMRT while maintaining target volume coverage.
Gesehen am 05.07.2022